2005
DOI: 10.1063/1.1998836
|View full text |Cite
|
Sign up to set email alerts
|

Guided ion-beam studies of the reactions of Con+ (n=2–20) with O2: Cobalt cluster-oxide and -dioxide bond energies

Abstract: The kinetic-energy dependence for the reactions of Co(n)+ (n=2-20) with O2 is measured as a function of kinetic energy over a range of 0 to 10 eV in a guided ion-beam tandem mass spectrometer. A variety of Co(m)+, Co(m)O+, and Co(m)O2+ (m < or = n) product ions is observed, with the dioxide cluster ions dominating the products for all larger clusters. Reaction efficiencies of Co(n)+ cations with O2 are near unity for all but the dimer. Bond dissociation energies for both cobalt cluster oxides and dioxides are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 71 publications
2
29
0
Order By: Relevance
“…[19][20][21] Their stability, structures, chemical reactivities, ionization energies, dissociation energies, and magnetic properties are engaging and challenging subjects. [22][23][24][25][26][27] Triggered by the above listed examples that illustrate the effect of dopant atoms on the properties of metal oxide clusters, we set out to investigate the influence of chromium dopants on the structure and stability of cobalt oxide clusters. These clusters likely have interesting magnetic properties, since Co and Cr, both 3d transition metals, are ferromagnetic and antiferromagnetic in bulk, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Their stability, structures, chemical reactivities, ionization energies, dissociation energies, and magnetic properties are engaging and challenging subjects. [22][23][24][25][26][27] Triggered by the above listed examples that illustrate the effect of dopant atoms on the properties of metal oxide clusters, we set out to investigate the influence of chromium dopants on the structure and stability of cobalt oxide clusters. These clusters likely have interesting magnetic properties, since Co and Cr, both 3d transition metals, are ferromagnetic and antiferromagnetic in bulk, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 is formed through a structure in which the carbon atom of CO is bonded to both the Co(III) and a neighboring oxygen atom. 28 [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] For cobalt oxide clusters, electronic and geometric structures for neutral and anionic CoO n (n = 1-4) clusters have been reported by Uzunova et al, and a dissociation channel, loss of a dioxygen molecule, is suggested based on their DFT calculations. 63 In addition, Co m O n À (m = 4-20, n = 0-2) anion clusters are generated by a laser ablation source and are investigated by photoelectron spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic energy dependence of reactions of metal cluster cations with O 2 has been studied for V n 20), and Ni n + (n = 2-18). [70][71][72][73][74] Most transition metal cluster cations (as well as neutrals) react with O 2 efficiently to form a cluster dioxide, reaction (11). The reaction efficiencies approach 100% of the collision cross section and rapidly reach the hard-sphere limit, as shown for the example of V 10 + in Fig.…”
Section: + -O Bond Energiesmentioning
confidence: 99%